A cooperative game approach for assessing the collision risk in multi-vessel encountering. (1st September 2019) - Liu, Zihao; Wu, Zhaolin; Zheng, Zhongyi
Abstract: Collision risk quantification is important for reducing collision accidents and improving navigational safety. However, most of the related studies attached more importance to the collision risk between two vessels, but failed to obtain the global collision risk in multi-vessel encountering. This paper proposed a model which was able to assess the collision risk not only between any two vessels but also among multiple vessels in encountering based on a cooperative game. For assessing the global collision risk, a new collision risk indicator was proposed based on collision avoidance manoeuvre and ship domain to represent the collision risk of each vessel in multi-vessel encountering first. Shapley value method was utilized to estimate the contribution of each vessel to the global collision risk. Global collision risk could be assessed based on the collision risk and contribution of each vessel. For validating the effectiveness of the proposed model, several experiments of different multi-vessel encountering cases were carried out. The results suggested that the model could represent the collision risk of multi-vessel effectively. The model can help surveillance operators have a better understanding of the global collision risk and lower their cognitive pressures faced with challenges from relative high traffic density or complexity. Highlights: A cooperative game-based multi-vessel collision risk assessing model was proposed. A new collision risk indicator based on collision avoidance manoeuvre was proposed. Shapley value method in cooperative game was utilized to estimate the contribution. The effectiveness of the proposed model was validated by various encountering cases. The proposed model can provide surveillance operators with assistance in monitoring.